Música para rezos y liturgias de la Semana Santa de los archivos misionales en Bolivia - Nawrot, Piotr (Annales Missiologici Posnanienses, 2019)
The present essay exposes the revision of some texts written by the missionaries and superiors of the Society of Jesus where it is narrated about the celebrations of Holy Week in the former Jesuit reductions among the South-American Indians. It speaks about music that was used in formal and popular liturgies of the Holy Week. We begin on Passion Sunday and continue until Holy Saturday, asking if – based on the music collections of the missions of Chiquitos and Moxos – it is possible to reconstruct the sound of these festivities according to what the texts written from the 18thcentury missions testify. The article includes the transcription of some of the musical works cited in the texts of the Jesuits. If in the conclusion of this study it is demonstrated that such a global reconstruction of the music of Holy Week is possible, the project could be deepened in another study as a natural continuation of this result.